Lymphoid Tissue Ontogeny in the Mummichog, Fundulus heteroclitus - Hunt, Laura R. (2008)
Most studies that examine the ontogeny of lymphoid organ development in teleostean fishes use species of interest to aquaculture or genetic research, and to date have focused on strictly marine or strictly freshwater species. The mummichog, Fundulus heteroclitus, also known as the estuarine killifish, is a unique model for studies on developmental immunobiology because it is euryhaline, has a high degree of thermal tolerance, and has a unique reproductive strategy. Embryonic and larval mummichogs were examined for the ontogeny of lymphoid tissue development. The first lymphoid organ to appear was the head kidney at 1 dph, followed by the spleen at 1 wph, and then the thymus at 3 wph. Rag-1 was partially cloned and sequenced and shown to be highly conserved among other vertebrate Rag-1 genes. Using QT-PCR to monitor the temporal expression of Rag-1 it was shown to reach a maximum intensity at 3- and 4-wph, and to then drop to pre-2 wph levels. Overall, this study suggests that juvenile mummichogs do not possess the ability to mount T- or B-cell responses until some time after 5-wph. Even though the estuarine killifish tolerates a wide range of salinities, the developmental patterns of lymphoid tissues are similar to what has been reported for strictly marine (stenohaline) teleosts. Thus, the mummichog should be a convenient model for understanding the developmental immunobiology of most marine teleosts.